Auditoria regular del municipio de Quimbaya Quindío para la vigencia 2014 (2015)
The regular review and audit is the examination conducted audit institutions to operations of different nature, made by control subjects in order to give a comprehensive opinion formed by the opinion of the financial statements and management concept and the results so we can issue a ruling on the demise of the account or not. For the particular case of this internship regulate the municipality of Quimbaya effective 2014, based on territorial audit guide (GAT) adopted by Resolution No. 207 of December 20, 2012, in the audit was conducted audit took into account each one phase, begun in the planning stage in which all the information provided during physical and magnetic media through the application SIA where by means of verifying the quality of the rendered information is determined to be known and verified, where it was observed some formats not present the requested information, for that reason it was required by the control authority.